If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-2)(x-3)=13
We move all terms to the left:
(x-2)(x-3)-(13)=0
We multiply parentheses ..
(+x^2-3x-2x+6)-13=0
We get rid of parentheses
x^2-3x-2x+6-13=0
We add all the numbers together, and all the variables
x^2-5x-7=0
a = 1; b = -5; c = -7;
Δ = b2-4ac
Δ = -52-4·1·(-7)
Δ = 53
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-\sqrt{53}}{2*1}=\frac{5-\sqrt{53}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+\sqrt{53}}{2*1}=\frac{5+\sqrt{53}}{2} $
| -12(3x-6)=-108 | | 9x-10x/12=3 | | 6(3x+6)=87 | | 2y+30=2(50)+30=130 | | 3b/4+b=14 | | 6(r-2)=24 | | 25=3y-10 | | Y=3n+70 | | 4x+30=4x+110=180 | | -3i=-10-2 | | 0.6x=43.5-2.3x | | q2+16q+63=0 | | 2y2-37y+161=0 | | 4m+3/5-2=12 | | 30-5x=30-14 | | 56y2-29y+3=0 | | 56y-29y+3=0 | | 10x2-101x+136=0 | | (x+2)*(x-3)=100 | | 28a=4a | | 3y2-10y+7=0 | | 7x2+62x-9=0 | | 3x(x-4)/x-0=0 | | 2x^2+x-312=0 | | 65=u+59 | | q+26=32 | | 83=s+95 | | 12v=81+3v | | 1/2r+4=r+10 | | 25=10y+6 | | 18x-2=308 | | 2x+44=6x+8 |